Oral Cannabidiol Use in Children With Autism Spectrum Disorder to Treat Related Symptoms and Co-morbidities - Barchel, Dana; Stolar, Orit; De-Haan, Tal; Ziv-Baran, Tomer; Saban, Naama; Fuchs, Danny Or; Koren, Gideon; Berkovitch, Matitiahu (Frontiers in Pharmacology, 2019)
Objective: Children with autism spectrum disorder (ASD) commonly exhibit comorbid symptoms such as aggression, hyperactivity and anxiety. Several studies are being conducted worldwide on cannabidiol use in ASD; however, these studies are still ongoing, and data on the effects of its use is very limited. In this study we aimed to report the experience of parents who administer, under supervision, oral cannabinoids to their children with ASD. Methods: After obtaining a license from the Israeli Ministry of Health, parents of children with ASD were instructed by a nurse practitioner how to administer oral drops of cannabidiol oil. Information on comorbid symptoms and safety was prospectively recorded biweekly during follow-up interviews. An independent group of specialists analyzed these data for changes in ASD symptoms and drug safety. Results: 53 children at a median age of 11yr (4-22) received cannabidiol for a median duration of 66 days (30-588). Self-injury and rage attacks (n=34) improved in 67.6% and worsened in 8.8%. Hyperactivity symptoms (n=38) improved in 68.4%, did not change in 28.9% and worsened in 2.6%. Sleep problems (n=21) improved in 71.4% and worsened in 4.7%. Anxiety (n=17) improved in 47.1% and worsened in 23.5%. Adverse effects, mostly somnolence and change in appetite were mild. Conclusions: Parents' reports suggest that cannabidiol may improve ASD comorbidity symptoms; however, the long-term effects should be evaluated in large scale studies.